2020
DOI: 10.3390/rs12010186
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Forest Stock Volume in Hunan Province, China, by Integrating In Situ Plot Data, Sentinel-2 Images, and Linear and Machine Learning Regression Models

Abstract: The forest stock volume (FSV) is one of the key indicators in forestry resource assessments on local, regional, and national scales. To date, scaling up in situ plot-scale measurements across landscapes is still a great challenge in the estimation of FSVs. In this study, Sentinel-2 imagery, the Google Earth Engine (GEE) cloud computing platform, three base station joint differential positioning technology (TBSJDPT), and three algorithms were used to build an FSV model for forests located in Hunan Province, sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 108 publications
4
40
0
1
Order By: Relevance
“…However, we found that the estimates were associated with uncertainties. The uncertainty of GSV estimates often results from atmospheric effects, sensor effects, sample plot GSV measurement errors, feature variable selection, and estimation model [ 27 , 59 ]. At present, the atmospheric effects and sensor errors cannot be completely eliminated [ 57 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we found that the estimates were associated with uncertainties. The uncertainty of GSV estimates often results from atmospheric effects, sensor effects, sample plot GSV measurement errors, feature variable selection, and estimation model [ 27 , 59 ]. At present, the atmospheric effects and sensor errors cannot be completely eliminated [ 57 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These images were acquired during the field investigation time on 22 September, 2017 ( Table 2 ). The official Sen2cor module version 2.5.5 was used to transform the Level-1C product into the Level-2A product [ 27 ]. The Level-2A product is the bottom-of-atmosphere corrected reflectance after radiometric calibration and atmospheric correction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations